Investigation of Antioxidant and Antimicrobial Activities of Different Extracts of Auricularia and Termitomyces Species of Mushrooms - Gebreselema Gebreyohannes; Andrew Nyerere; Christine Bii; Desta B. Sbhatu (The Scientific World Journal)
Mushrooms produce a variety of bioactive compounds that are known to have a potential source of antioxidant and antimicrobial properties. Natural antioxidants can protect against free radicals without any side effects. The purpose of this study was to evaluate the antioxidant and antimicrobial activities of Auricularia and Termitomyces extracts. Specimens of Auricularia and Termitomyces spp. were collected from Kakamega National Reserve Forest in Kenya. Specimens were identified, extracted, and screened for their antioxidant and antimicrobial activities using stable free radical DPPH and colorimetric bioassay methods, respectively. The antimicrobial activity of the extracts was tested against Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Staphylococcus aureus, MRSA, Candida albicans, and Candida parapsilosis. The maximum scavenging activity of hot water extract of Auricularia spp. was observed at 70.4% with the IC50 value of 40 μg/mL. Of the three extracts of Termitomyces spp., 70% ethanol extract has shown the highest scavenging activity (63%) with the IC50 value of 50 μg/mL. Chloroform and hot water extracts of Auricularia have shown statistically significantly different antifungal activities against C. parapsilosis (df = 2, F = 22.49, p ≤ 0.05). Of all the organisms, S. aureus was highly susceptible to 70% ethanol and hot water extracts of Termitomyces spp. with minimum inhibitory concentration values of 0.67±0.29 mg/mL. S. aureus and E. coli were the most susceptible and resistant bacteria to the hot water extract, respectively. In conclusion, the extracts of Auricularia spp. and Termitomyces spp. have shown promising antimicrobial and antioxidant activities.